2012
DOI: 10.1002/14651858.cd001167.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobials for treating symptomatic non-typhoidal Salmonella infection

Abstract: Background Non-typhoidal Salmonella (NTS) commonly causes diarrhoea, and is usually self-limiting, although sometimes people become ill with sepsis and dehydration. Routine antibiotic use for this infection could result in persistent colonization and the spread of resistant bacterial strains. Objectives To assess the e icacy and safety of giving antibiotics to people with NTS diarrhoea. Search methods We searched the Cochrane Infectious Diseases Group trials register (up to August 2012), the Cochrane Controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 49 publications
3
79
0
5
Order By: Relevance
“…Antimicrobials are not recommended for treatment of immunocompetent adults or children more than 1 year of age who present with mild to moderate gastroenteritis caused by Salmonella. This recommendation is supported by a meta-analysis of 12 trials that found no significant benefit from antibiotic therapy on the duration of illness, diarrhea, or fever [57]. Antibiotic therapy has not been shown to shorten the duration of symptoms and in fact may prolong colonization and carrier stage.…”
Section: Nontyphoidal Salmonellamentioning
confidence: 99%
See 2 more Smart Citations
“…Antimicrobials are not recommended for treatment of immunocompetent adults or children more than 1 year of age who present with mild to moderate gastroenteritis caused by Salmonella. This recommendation is supported by a meta-analysis of 12 trials that found no significant benefit from antibiotic therapy on the duration of illness, diarrhea, or fever [57]. Antibiotic therapy has not been shown to shorten the duration of symptoms and in fact may prolong colonization and carrier stage.…”
Section: Nontyphoidal Salmonellamentioning
confidence: 99%
“…In infants less than 3 months of age, antimicrobial treatment is recommended because these patients are at higher risk for bacteremia and extra-intestinal complications such as meningitis and osteomyelitis [40][41][42]58]. Use of antimicrobials should also be considered in children with underlying medical conditions, such as HIV infection, primary immunodeficiency disorders, sickle cell anemia, chronic gastrointestinal disease, and cancer; nevertheless, the efficacy of this measure is unproven [57].…”
Section: Nontyphoidal Salmonellamentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to antibiotics has strong implications for the clinical treatment of severe cases of salmonellosis (28). No statistically significant correlations were observed between resistance to antibiotics and survival in low-aw broths, suggesting that Salmonella exposed to these low water environments, in this collection, would not have increased survival after antibiotic treatment.…”
Section: Discussionmentioning
confidence: 78%
“…These include neonates and young infants (< 6 months) and children with underlying immune deficiency, anatomical or functional asplenia, corticosteroid or immunosuppressive therapy, IBD, or achlorhydria (weak recommendation, low-quality evidence). A Cochrane systematic review showed that antibiotic therapy of Salmonella gastroenteritis does not significantly affect the duration of fever or diarrhea in otherwise healthy children or adults compared to placebo or no treatment [76]. Moreover, antibiotics were associated with a significant increase of carriage of Salmonella, although other adverse events were not reported.…”
Section: Pathogen-based Approachmentioning
confidence: 99%